Sistem Informasi Penjualan Kambing Etawa Berbasis Web Menggunakan Metode First In First Out (FIFO) - Yuli Artika; Edy Rahman Syahputra; Hasdiana Hasdiana (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Etawa goats are a crossbreed between the Jamnapari goats from India and local Indonesian goats. Based on the products they yield, Etawa goats are classified into several types: those that produce meat, those that produce milk, and those that provide skin for crafts. Technological advancements have significantly transformed how farmers manage and sell Etawa goats. With web-based information systems, e-commerce platforms, and health monitoring technology, farmers can increase operational efficiency, expand market reach, and ensure the quality of their goats. Technology not only supports business sustainability but also offers a competitive advantage in the Etawa goat farming industry. One problem that arises is in managing sales data for Etawa goats. When a product is ordered and payment is made, the purchased item should no longer be available. However, due to a lack of communication from the seller about out-of-stock products, other buyers may attempt to purchase the same item. If payment is made but the product is unavailable, the seller must refund the buyer without any deductions. Therefore, a web-based information system using the FIFO method is needed to help sellers manage outgoing products. The FIFO method ensures that orders are processed on a first-come, first-served basis, continuing with the available stock for sale. With a web-based sales information system for Etawa goats, sellers can easily manage their sales records.